RANCANG BANGUN SISTEM INFORMASI PENJUALAN BARANG SECARA TUNAI - Marlina Marlina (LPPM Universitas Bina Sarana Informatika, 2018)
The development of science and technology has developed rapidly. Everything is demanded to be done quickly and accurately. This can be realized with the maximum use of technology. Technology in this case is a computer that is very necessary, including in the world of commerce, with Computerization Systems the problems that exist in this company, especially in terms of data processing can be overcome properly, and with a computerized system can be achieved an effective and efficient activity in supporting activity at CV Prima Inti Anugrah this is because manual data processing in the company often occurs late in processing sales reports. This certainly hampers the company's objectives. So we need a sales program that is made using Microsoft Visual Basic 6.0 software. With Computerization as an alternative problem solving that can overcome the problems faced by manual systems. Among them can minimize errors that may occur and facilitate the search for data needed.